Public Policy and Experiences of Aging: Social Relationships and Social Integration in Chilean Policy on Aging. Issue 1 (2nd January 2022) - Torrejon, Maria-Jose; Martin-Matthews, Anne
ABSTRACT: This study uses an interpretive narrative approach to compare and contrast assumptions regarding social integration (participation in meaningful and multiple roles, and engagement in social networks) as promoted in the Chilean Comprehensive Policy for Positive Aging, with the expectations of interviewees aged 60 to 74 years. The Policy assumes specific forms of social integration by: offering different options of social integration to dependent vs. independent older people, encouraging autonomy and self-management, and assuming the primacy of family responsibility in older people's care. Both the Policy and the interviewees emphasize the value of autonomy and independence in old age; the latter, however, do not place family at the frontline when care is needed. Understanding the matches and gaps between policy assumptions and older people's expectations for social integration, including the role of family caregiving, can open new possibilities to prevent social isolation and promote different forms of social support that are valued by older adults for their emotional and practical benefit.